Vortexlike topological defects in nematic colloids: chiral colloidal dimers and 2D crystals. - Tkalec, U; Ravnik, M; Zumer, S; Musevic, I (2009)
We show that chiral ordering of the underlying complex fluid strongly influences defect formation and colloidal interactions. Nonsingular defect loops with a topological charge -2 are observed, with a cross section identical to hyperbolic vortices in magnetic systems. These loops are binding spontaneously formed pairs of colloidal particles and dimers, which are chiral objects. Chiral dimer-dimer interaction weakly depends on the chirality of dimers and leads to the assembly of 2D nematic colloidal crystals of pure or "mixed" chirality, intercalated with a lattice of nonsingular vortexlike defects.